Analisis Potensi Bahaya Dengan Menggunakan Metode Identification And Risk Assessment (HIRA) Dan Job Safety Analysis (JSA) Pada PT.XYZ - Ahmad Irfandi Halifasa; Ayudyah Eka Apsari (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
PT XYZ is a metal industry company that produces drinking water pipe joints with specifications of gray cast iron and round graphite cast iron. The problems that exist in PT. XYZ are the lack of implementation of occupational safety and health in each process area of the production floor with the aim of research analyzing potential hazards, knowing risk level assessments, and controlling recommendations. The HIRA method calculates that there are 3 risk categories for occupational accident risk assessment with 10 high risk categories with a percentage of 41.66%, 12 moderate risk categories with a percentage of 50% and 2 low risk categories with a percentage of 8.33%. The JSA method results from calculating KPIs for low risk categories with a range of 0 to 2.33, medium risk categories with a range of 2.33 to 4.66, high risk categories with a range of more than 5.25. Calculation of the T-Test Test obtained the difference value before the control recommendation and after the control recommendation was 7.875 and the t value was 7.814 by obtaining a p-value of 0.00 so it is less than an alpha value of 0.05.